Routledge handbook of international statebuilding - Chandler, David , 1962-; Sisk, Timothy D. , 1960- (Routledge, 2013)
"This new Handbook offers a combination of theoretical, thematic and empirical analyses of the statebuilding regime, written by leading international scholars. Over the past decade, international statebuilding has become one of the most important and least understood areas of international policy-making. Today, there are around one billion people living in some 50-60 conflict-affected, 'fragile' states, vulnerable to political violence and civil war. The international community grapples with the core challenges and dilemmas of using outside force, aid, and persuasion to build states in the wake of conflict and to prevent such countries from lapsing into devastating violence. The Routledge Handbook of International Statebuilding is a comprehensive resource for this emerging area in International Relations. The volume is designed to guide the reader through the background and development of international statebuilding as a policy area, as well as exploring in depth significant issues such as security, development, democracy and human rights. Divided into three main parts, this Handbook provides a single-source overview of the key topics in international statebuilding: Part One: Concepts and Approaches ; Part Two: Security, Development and Democracy ; Part Three: Policy Implementation. This Handbook will be essential reading for students of statebuilding, humanitarian intervention, peacebuilding, development, war and conflict studies and IR/Security Studies in general."